Perilaku Pengusaha Truck Trailer dalam Pelayanan Jasa di tinjau dari Etika Bisnis Kota Surabaya: (Studi Kasus CV. Global Jaya Samudra) - Peppy Nur Ansondi; Rika Yuliastuti (PUTRA JAWA PUBLISHER, 2023)
This study aims to determine the behavior of Joint Trailer Truck entrepreneurs towards customers and to find out the review of Business Ethics in service behavior. This research uses qualitative methods with primary data collection techniques in the form of interviews and data analysis techniques used in the form of data collection, data reduction and conclusions. the results of this study are service behavior at CV Global Jaya Samudra in Surabaya city is still bad or not good. This research is proven based on the results of interviews with customers or tenants in these services. Informants said that service to tenants was still not good. Meanwhile, good service ethics must fulfill the following 5 principles (1) tawhid, (2) responsibility, (3) balance or justice, (4) free will, (5) virtue.